Thermocapillary pumping of a droplet in a closed microchannel - Odukoya, A. (Knovel, 2011)
"Examines methods for determining the droplet displacement that results from thermocapillary pumping in a closed microchannel"--Description from Knovel website.
Keywords: Heat pumps.; elektronické knihy; electronic books